O processo de criação do advergame e o uso do videogame na publicidade - Lazarini, Filipe Beneli (2011)
The present study exposes the processes of creation and use of the advergame and videogame in advertising as a communication tool. Aims to present a study on the procedures present in the creative development of an advergame and discuss the use of advergames /videogames as a diffuser channel of communication in advertising. Starting with the premise that games can be stimulating and purchase facilitators when used in advertising. The research is based on theoretical studies of narratives in games made by Janet Murray, Sergio Nesteriuk, Renata Gomes and Lucia Santaella, and on studies of games by Huizinga. Reflections on the new media are anchored in the writings of Lucia Leão and analysis of creative processes of Cecilia Salles. It proposes an archaeological journey to the problem and, therefore, is part of the study analyzing the use of film media by advertising. Advertising communication is focused according the hybridization concept developed by Covaleski. The game is understood as an experience of communication for marketing purposes, especially for its applications as interactive advertising processes. The discussion about the process of creating a specific advergame is based on the studies developed by Salles, besides the experiences of the author of this dissertation